2014
DOI: 10.1089/pho.2014.3729
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficacy of LED-Laser Treatment and Control of Tooth Sensitivity During In-Office Bleaching Procedures

Abstract: LED-laser treatment was not able to prevent or reduce the sensitivity of teeth and did not improve the efficacy of bleaching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…De Almeida Farhat et al discussed that efficacy of LED-laser when used with high concentration of bleaching agent produced lesser sensitivity comparatively with all other factors [15].…”
Section: Discussionmentioning
confidence: 99%
“…De Almeida Farhat et al discussed that efficacy of LED-laser when used with high concentration of bleaching agent produced lesser sensitivity comparatively with all other factors [15].…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of this study are consistent with the results of Gurgan et al (Gurgan et al 2010) who found that bleaching with a diode laser was associated with less tooth and gingival sensitivity, and so this method might be preferred among the in-office systems. In contrast, some studies found that laseractivated bleaching had no effect on or even increased postoperative dental sensitivity (Farhat et al 2014;Giudice et al 2016).…”
Section: Groupmentioning
confidence: 95%
“…In theory, the light source, by energizing hydrogen peroxide (H 2 O 2 ), increases the rate of oxygen decomposition, accelerates the release of reactive oxygen species, and thus enhances the breakdown of carbon double bonds present in the chromophores of the teeth [1]. Although it is a highly popular technique in dental practice, it raises some concerns, particularly regarding the adverse effect of dental sensitivity [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Factors such as the concentration of the gel and the application protocol in uence the intensity of this exposure and subsequent damage [12][13][14]. The use of LED light sources has also been associated with sensitivity [1,15], increased pulp temperature [1,5,16], and appears to have no signi cant improvement in color effectiveness [13,[16][17][18]. Therefore, it is important to evaluate the biological repercussions that this treatment modality may have on the pulp tissue.…”
Section: Introductionmentioning
confidence: 99%